Strategies of Optimizing VMS to preventing IUU fishing by Indonesian fishermen in Papua New Guinea - Kolis, Mat; Rulinawaty; Daulay, Pardamean (GoAcademica Research & Publishing, 2024)
Illegal, unreported, and unregulated (IUU) fishing presents a substantial obstacle to the effective administration of maritime affairs, specifically in areas such as Papua New Guinea, where Indonesian fishermen partake in unlawful operations within the Exclusive Economic Zone. The primary objective of this research endeavor is to assess the effectiveness of policy interventions that target IUU fishing by Indonesian seafarers in Papua New Guinea, with a specific emphasis on the deployment of vessel monitoring systems (VMS). This research identifies significant challenges and assesses alternative approaches for improving VMS policies by employing the Analytical Hierarchy Process (AHP). The findings underscore the significance of involving stakeholders, adhering to legal and regulatory requirements, and the consequences for maritime security. Identifying education and training as the most crucial options emphasizes the importance of equipping stakeholders with the essential knowledge and abilities to efficiently utilize VMS technology. The study also stresses how important it is for agencies to work together, for VMS coverage to grow, and for infrastructure to be improved in order to make policies more effective. The Indonesian Government can enhance its regulatory capabilities regarding illegal, unregulated, and unreported (IUU) fishing, thereby promoting maritime security and sustainable fisheries management in the region, by placing an equal emphasis on education and training in conjunction with these supplementary measures.